Genome-scale metabolic modelling reveals interactions and key roles of symbiont clades in a sponge holobiont - Shan Zhang; Weizhi Song; Geogios Marinos; Silvio Waschina; Johannes Zimmermann; Christoph Kaleta; Torsten Thomas (Nature Communications)
Abstract Sponges harbour complex microbiomes and as ancient metazoans and important ecosystem players are emerging as powerful models to understand the evolution and ecology of symbiotic interactions. Metagenomic studies have previously described the functional features of sponge symbionts, however, little is known about the metabolic interactions and processes that occur under different environmental conditions. To address this issue, we construct here constraint-based, genome-scale metabolic networks for the microbiome of the sponge Stylissa sp. Our models define the importance of sponge-derived nutrients for microbiome stability and discover how different organic inputs can result in net heterotrophy or autotrophy of the symbiont community. The analysis further reveals the key role that a newly discovered bacterial taxon has in cross-feeding activities and how it dynamically adjusts with nutrient inputs. Our study reveals insights into the functioning of a sponge microbiome and provides a framework to further explore and define metabolic interactions in holobionts.